One hundred wishes - Enid Richemont (London, Franklin Watts, 2019)
Miserable, old Stan lives on his own, just counting his money. And when his fairy godmother grants him three wishes, all he can think of is wishing for more wishes and greedily hoarding them. But the wishes escape, and Stan's world is about to get a whole lot brighter. This story celebrates friendship, however it may find you